Evaluation of INFγ in serum of Crohn’s patients by using ELISA technique - Aliah H. Mustafa; Hayfaa M. Fahad; Nawar S. Khalil (University of Thi-Qar Journal of Science, 2025)
Crohn’s disease, a chronic inflammatory bowel disorder that can cause gradual intestinal damage and an impairment. CD can affect people of all ages, from children to the elderly, and can causes a considerable morbidity and reduce the quality of life. The main aim of this study was to explore the serum level and evaluate the predictive role of immunological parameters of Interferon gamma (INF-γ) for the detection of an active disease in Crohn’s patient. The current investigation, 70 blood samples acquired from Crohn’s disease patients and 70 apparently healthy individuals were used. A sandwich ELISA kit (No: E-EL-H0108) U.S.A. was used to determine serum levels of INF-γ that contribute to disease progression. A total of 140 samples (70 cases and 70 controls) were collected in a 1:1 ratio, with each participant was screened base on inclusion and exclusion criteria. This study encourages employing INF-γ as a predictive biomarker for Crohn’s disease.